Development of a precision agriculture downloadable content for the farming simulator game - Pavlenko, Tetiana; Argyropoulos, Dimitrios; Arnoult, Matthieu; Engel, Thomas; Murdoch, Alistair J.; Griepentrog, H.W.; Kambuta, Jacob; Latherow, Tamisan; Tranter, Richard; Paraforos, Dimitrios S.; Gadanakis, Yiorgos (My University, 2023)
Precision Agriculture (PA) offers solutions enabling informed decision-making on farms and contributes to agricultural sustainability. However, despite the evidence-based benefits of PA, the adoption of different related technologies at the farm level is slow. One of the approaches for increased awareness and delivering knowledge about the advantages of PA is education. To address this issue, a study in the scope of an EIT-Food-funded project was aimed at integrating the main principles of PA into an existing game. The PA module can be considered a novel and innovative way to communicate the benefits of PA and encourage stakeholders to adopt its principles.
Keywords: Precision Farming; Downloadable Contente; Economic performance; Environmental performance; Education; Gamification